Biological potential and therapeutic effectiveness of pteryxin in medicine. A viable alternative to current remedies for the treatment of human disorders - Kanika Patel; Dinesh Kumar Patel (Elsevier, 2024)
Background: Herbal medicine, including Chinese herbal medicines is getting attention in the scientific research due to their long historical applications and reliable therapeutic efficacy. Coumarin is a secondary metabolites found to be present in different species of plants. Pteryxin is a coumarin found to be present in the Peucedanum praeruptorum, Pteryxia terebinthina, Radix Peucedani, Qian-Hu and different Apiaceae plants. Methods: Present paper will explore and highlights the key scientific information pertaining to the reported activities of coumarin class phytochemical pteryxin. In the present work, scientific data of pteryxin were collected from Google, Scopus, PubMed, Science Direct and Google Scholar scientific databases using the keywords coumarin, phytochemical and pteryxin. Results: The scientific information collected from various data sources reveals the biological potential of pteryxin in the management of bone loss, seizures, acute lung injury, inflammatory conditions, Alzheimer's disease, hyperglycemia, liver injury, uropathogenic condition, and SARS-cov-2 infection. Additionally, pteryxin also possesses vasorelaxant and antioxidant activity. In this work, analytical aspects like separation, isolation and identification of pteryxin in different samples has also been discussed. Present work summarized the mechanistic insights into the medicinal importance and translational scope of pteryxin for the treatment of human disorders and associated secondary complications. Conclusion: On the basis of existing information on pteryxin, it may be concluded that there is need to rigorous examine the potential of pteryxin through various preclinical and clinical studies to explore its potential as a therapeutic lead molecule. Pteryxin may also be explored to develop functional bioactive molecules through structural modification.